Temporal Land-use Change Analysis of Patiala-Ki-Rao Watershed in Shivalik Foot-Hills using Remote Sensing and GIS - Sushanth, Kallem; Bhardwaj, Anil; C, Loshali D.; B., Pateriya (Journal of Agricultural Engineering, 2019)
Land-use change due to urbanization is continuously decreasing agricultural and forest lands that has important implications on the sustainable livelihood of the inhabitants of a watershed. In this study, land-use maps of Patiala-Ki-Rao watershed that is located in Shivalik foot-hills in Mohali district, Punjab were generated in GIS environment using Landsat imageries for the years 2006 and 2016 with overall classification accuracy and Kappa statistic of above 90 % and 0.9, respectively. The analysis of land-use maps indicated that the area under all land-uses decreased over a decade, except built-up land that increased by 372.27 ha (112.04 %) mainly due to urbanisation in the watershed. The change detection matrix revealed that out of 906.98 ha under agricultural land in 2006, 197.43 ha were mainly converted to built-up land. Likewise, from forest cover of 3462.21 ha in 2006, 151.11 ha were converted to agricultural land and 75.05 ha to built-up land. These land-use changes, if continued, may cause a serious threat to watershed resources, and hence calls for proper land-use policy formulation.